2020
DOI: 10.1093/asj/sjaa092
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cosmetic Surgery Tourism: Case Series and Cost Analysis

Abstract: Background Cosmetic surgery tourism is increasing exponentially. Patients seek cosmetic procedures within the United States and abroad, lured by lower cost procedures, shorter waiting lists, and affordable airfare and hotel accommodations. Unfortunately, operations are often performed by non–board-certified plastic surgeons, sometimes not even by plastic surgeons. Preoperative counseling, frequently limited to a video-chat with an office secretary, provides inadequate discussion regarding pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Recent analysis has shown that cosmetic surgery performed overseas carries significantly higher risks of complications, notably infection. 10…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis has shown that cosmetic surgery performed overseas carries significantly higher risks of complications, notably infection. 10…”
Section: Discussionmentioning
confidence: 99%
“…This is a similar issue that overseas groups find when trying to assess the impact of complications arising from cosmetic surgery tourism on their own health systems. 7,8,[10][11][12] Some articles have attempted metaanalyses of a number of papers documenting treated complications but again the numbers are low and it is hard to assess the true impact. 9,19 Furthermore, while we may have some gauge on the medical complications, there is no literature assessing patient-reported outcomes or aesthetic outcomes from cosmetic surgery tourism.…”
Section: Discussionmentioning
confidence: 99%
“…5 The number of patients who receive cosmetic surgery overseas is unknown, and the numbers who have complications arising from this treatment are not accurately known either. Literature from overseas studies shows a measurable cost in the treatment of complications arising from cosmetic surgery tourism [6][7][8] and reflects the morbidity patients experience from complications arising from surgery in other countries. 9 Internationally there are concerns about infectious disease transmission of antibioticresistant bacteria from overseas surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is likely to be a difficulty with liaison with the surgeon after the patient has returned home, as well as difficulty in access to overseas surgical and hospital records. 39,40 The literature on such issues is growing with a review of 26 English patients who returned from overseas where they had undergone cosmetic procedures, in particular abdominoplasties and gluteal enhancement surgery, having complications costing the National Health Service an average of £5883 ($11095AUD) per patient. 41 The authors argued that 'Global governing bodies should focus efforts on educating patients and raising awareness on the everprevalent issue'.…”
Section: Cosmetic Surgery Tourismmentioning
confidence: 99%
“…The literature suggests that perioperative infections, including infections that may be antibiotic resistant, issues with blood transfusions in countries where blood products are not well monitored, and inadequate post‐operative care are amongst the risks run by persons who travel abroad for cosmetic surgery. In addition, there is likely to be a difficulty with liaison with the surgeon after the patient has returned home, as well as difficulty in access to overseas surgical and hospital records 39,40 . The literature on such issues is growing with a review of 26 English patients who returned from overseas where they had undergone cosmetic procedures, in particular abdominoplasties and gluteal enhancement surgery, having complications costing the National Health Service an average of £5883 ($11095AUD) per patient 41 .…”
Section: Cosmetic Surgery Tourismmentioning
confidence: 99%